Biodegradation of organophosphorus insecticide methyl parathion by soil microorganisms - Le Thi Hue; Hoang Quang Cuong; Vu Dinh Duy; Vo Thi Hoai Thu (E3S Web of Conferences, 2021)
Organophosphorus compounds (OPs) have been widely used as effective insecticides. As a result, using too many OPs causes the residues of pesticides to be washed away into the water or soil, not only polluting water and soil, also directly or indirectly affecting environment and human health. Besides many countries and terrorists also use them as chemical warfare weapons. They are very dangerous neurotoxins to humans, animals and the environment. In the soil, there are many microorganisms that can degrade OPs, helping to release the accumulation of these toxic substances. In this study, two effective OP-degrading bacterial strains P9 and H14 has been isolated from agricultural land in Ha Nam province, Vietnam. We had used DNA barcodes (16S rRNA) to molecular identification of Klebsiella variicola (P9) and Priestia aryabhattai (H14) and deposited in GenBank MW644772, MW644771, respectively. Moreover, at an initial concentration of methyl parathion 50 mg/L, in investigative culture mediums and conditions, strain P9 degraded 100% of methyl parathion after 7 days in Luria-Bertani (LB) liquid culture. Maximum growth of P9 strains was observered after 6 days incubation (OD600=3.34). This study is an effort to open a direction of applying them in the treatment of OPs contaminated soils and water.